Use of Online Pubic Access Catalogue by the Research Scholars of Guru Nanak Dev University, Amritsar: a Study - Narang, Asha; Singh, Sukhdev (Journal of Information and Knowledge, 2013)
Information technology has played a crucial and constructive role in the modernization of information services. It has significantly helped the librarians in providing right information to right users at right time. Its applications have brought a sea change in the techniques of information access, dissemination, storage and retrieval. Online Public Access Catalogue (OPAC) is a service that helps the users in speedily finding their required documents. This study is an attempt to ascertain the use and opinion about OPAC in Bhai Gurdas Library, Guru Nanak Dev University, Amritsar by the research scholars. On the basis of analysis of data, major findings and suggestions put forth by the respondents about the expectations and gaps have been given in this study.